From English to First-Price Sealed Bid: An Empirical Assessment of the Change in Auction Type on Experienced Bidders - Joshua J. Miller (Review of Economic Perspectives, 2014)
This paper estimate the differential impact of first-price sealed-bid (first-price) auctions relative to English auctions on auction revenue. While there is a theoretical literature on the potential outcomes of first-price relative to English auction, there is a paucity of articles that empirically estimate this relationship. The answer to this question is important not only to economists but also those designing auction for practical application. Using a unique dataset from tax lien auctions in Illinois, I empirically test the effect of a switch in auction type from English to first-price. I find auction revenue is greatly increased, by as much as 22 percent, under the first-price auction. The results are supported by a within county difference-in-difference model specification and are robust when restricting the sample across various specifications
Keywords: 330